Q plus r equals s so t plus u equals?

Updated: 4/28/2022
User Avatar

Wiki User

14y ago

Best Answer


User Avatar

Wiki User

14y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: Q plus r equals s so t plus u equals?
Write your answer...
Still have questions?
magnify glass
Related questions

Evaluate q-r if q equals -13 and r equals -2?


How do you do 12q plus r equals 448?

How many twelves can you put into 448 without going over? 37(37=q). You will get 444. subtract 444 from 448 and you get 4(4=r) So q=37 and r=4.

What is p plus r plus q plus 113 plus 80 plus 54?

p + r + q + 175

What is b plus g plus h plus h plus r plus v plus x plus z plus q plus a plus p plus l plus f plus g plus d equals?


'p q' means p is wife of q and p plus q means p is father of q and p q means p is sister of q than g h plus r d how is g relatied th d?

g h plus r d g is the sister of (h plus (r is a sister of d)) g is the sister of h is the father of r is the sister of d so g is d's aunt.

R plus 16 equals 5r-10?

so 26 = 4r so r = 6½

If a equals 1 b equals 2 z equals 26 what is p plus q plus r?

Starting with the information that is given: Two options, due to the lack of punctuation: a=1b=2z=26 -or- a=1 b=2 z=36 p=(not defined) q=(not defined) r=(not defined) Therefore, all we can assert from the given information is that p+q+r = p+q+r (the variables can be rearranged without altering the (unknown) value, because of the commutative property of addition. a, b and z are not used in the equation, so their values are irrelevant. p, q and r are not defined, so we cannot assume any value for any of the variables in the equation. Well, we could assume, but it would be just that - an assumption, and an unfounded assumption at that. There was not enough information provided to draw any more concrete conclusion.

Pq equals 3p plus 4r minus 2p?

Without prior knowledge of the value of q or r, it is impossible to calculate the answer to this equation.

P varies jointly as q r and s One set of values is p equals 70 q equals 7 r equals 5 and s equals 4 Find p when q equals 2 r equals 15 and s equals 7?

If P varies jointly as q, r and s - assume this is in direct proportion, then P ∝ qrs so P = kqrs where k is a constant.70 = k x 7 x 5 x 4 = 140k : k = 140/70 = 0.5When q = 2, r = 15 and s = 7 then,P = 0.5 x 2 x 15 x 7 = 105

P 2x-9y q 5y plus 6-4x r 3x plus 3y-5 then p plus q plus r?

p + q + r = (2x - 9y) + (5y + 6 - 4x) + (3x + 3y - 5) = x - y + 1

Evaluate pq - r when p equals 3 q equals 4 and r equals -6?

pq-r, if p is 3, q is 4, and r is -6 is equal to 3 x 4 - (-6), which is equal to 12 + 6, which is equal to 18.

Pqr when p equals 2 q equals 4 andd r equals 5?

PQR P=2 Q=4 R=5 2 x 4 x 5 = 40